Adsorption Properties of Azadirachta indica Extract on Corrosion of Aluminium in 1.85 M Hydrochloric Acid - K.O., Ajanaku; O., Aladesuyi; C.O., Ajanaku; E. A., Adedapo; A. A., Akinsiku; F.E., Sodiya (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2015)
The crude extract of Azadirachta indica was used in the corrosion inhibition study of aluminium metal coupons in 1.85 M hydrochloric acid environment by gasometric technique. The coupons were immersed in test solutions of uninhibited 1.85 M HCl and those containing extract concentrations of 10%, 20%, 30%, 40% and 50% (v/v) at room temperature. The rate of the reaction was captured by monitoring the volume of hydrogen gas evolved as a result of the interaction. The inhibition efficiency of the extracts and the adsorption isotherm of the process were calculated using Frumkin, Freundlich, Langmuir and Temkin adsorption theories and the surface morphology studied using Scanning Electron Microscopy (SEM). It was observed that the plant extract retarded the acid induced corrosion of aluminium and the volume of hydrogen gas evolved reduced with increasing extract concentration. The adsorption studies revealed that Langmuir isotherm is the best model for the adsorption of Azadirachta indica (R2 = 0.999) on aluminium surface. This implied that the Azadirachta indica extracts with aluminium metal undergoes chemisorption.